OC-093 A pragmatic multicentre randomised controlled trial comparing stapled haemorrhoidopexy to traditional excisional surgery for haemorrhoidal disease. the ethos trial. (22nd June 2015) - Watson, AJ; Bruhn, H; Macleod, K; McDonald, A; McPherson, G; Kilonzo, M; Norrie, J; Loudon, MA; McCormack, K; Wood, J; Cook, JA
Abstract : Introduction: Haemorrhoidal disease is common in all age groups from the mid-teens onwards. Approximately 25, 000 procedures were performed in England during 2006/2007 on hospital day-cases or inpatients. 1 Current interventions include traditional excisional surgery (TH) and stapled haemorrhoidopexy (SH). Uncertainty remains about how they compare. 2–6 The primary aim of eTHoS is to assess whether there is a difference between SH and TH 7 for the treatment of haemorrhoidal disease (grades II, III, and IV) on patient centred quality of life profile. Treatment costs will also be examined. Method: Participants were randomly allocated to one of two study groups in equal proportion (SH or TH). Thirty-one sites from within the UK took part in the study. Patients, aged 18 year or older, with a diagnosis of circumferential haemorrhoids grade II–IV were eligible to take part. Randomisation utilised a minimisation algorithm which incorporated centre, grade of haemorrhoid (s), baseline EuroQol 5 Dimension health status questionnaire (EQ-5D) score and gender. The primary outcome for this study is patient-centred, quality of life profile (area under the curve (AUC) derived from EQ-5D data collected at baseline, 1 week, 3 weeks, 6 weeks, 12 months and 24 months; Economic, incremental cost per quality adjusted life year (QALY) gained with QALYs were based on the responses to the EQ-5D. A sample size of n = 338 per group was calculated to provide 90% power to detect a difference in the mean area under the quality of life curve of 0.25 standard deviations (derived from EQ-5D score measurements, with a significance level of 5%). 400 were to be randomised to each group. Results: The eTHoS trial closed for recruitment in August 2014 and is in follow-up. A total of 1129 patients were approached to take part in the trial. 777 participants were randomised (388 to TH and 389 to SH) with 7 post-randomisation exclusions from each group. Conclusion: This trial is currently the largest of its type in the world. Our results will be reported in full in October 2016 to The National Institute for Health Research. Disclosure of interest: None Declared. References: NHS Information Centre UK; http://www.hesonline.nhs.uk/servlet/ContentServer?siteID=1937&catergoryID-215 Shao WJ, et al . Br J Surg. 2008;95(2):147–60 Jayaraman S, et al . Dis Colon Rectum. 2007;50(9):1297–305 Burch J, et al . Health Technol Assess. 2008;12(8) Thaha MA, et al . Gut 2009;58(5):668–78 Shanmugam, et alet al. Colorectal Dis. 2010;12:579–86 Watson, et alet al. Trials 2014;15:439